Comparison of Toxicity and Toxicokinetics/Pharmacokinetics of an α1L-Adrenoceptor Agonist in Rats and Rhesus Monkeys - Takehisa Matsumaru; Reiko Sugiura; Kenji Sakai; Takashi Igarashi; Takayoshi Kuno (Elsevier, 2005)
We have investigated the toxicity of an α1L-adrenoceptor agonist, ESR 1150 CL, and compared the toxicokinetics and pharmacokinetics in rats and monkeys. In rats, this compound induced death with remarkable sacculated aneurysms of the aorta in groups given more than 3mg/kg per day in a 4-week repeated oral administration study. On the other hand, these findings were not observed in monkeys during a 2-week repeated oral administration study at doses up to 30 mg/kg per day. Orally administered ESR 1150 CL raised blood pressure transiently and dose-dependently during the 4-week repeated study in rats, whereas no increase of blood pressure was observed during the 2-week oral toxicity study in monkeys. Contrary to our expectation, the exposure level of ESR 1150 CL in rats was not higher than that in monkeys in the toxicokinetic evaluation. Pharmacokinetic evaluation indicated good absorption of the compound, but the bioavailability was very low in both rats and monkeys. These findings suggest that the potent species difference in toxicity of ESR 1150 CL between rats and monkeys does not depend on differences of toxicokinetics/pharmacokinetics. Rather, we suggest that the reason is likely to be species difference in the biological susceptibility of the α1L-adrenoceptor subtypes between rats and monkeys, which would be closely related with the effect on blood pressure by α1L-adrenoceptor agonist. Keywords:: α1L-adrenoceptor agonist, species difference (rat and monkey), toxicokinetics